Evaluasi Elemen Penilaian Praktik Pemberian Makanan Pendamping ASI untuk Pencegahan Risiko Stunting di Era Pandemi Covid-19: Studi Pada Balita Indonesia, < 5 tahun (Rapid Review): Kajian Elemen Pemberian Makan Balita sebagai Upaya Pencegahan Stunting di Saat Pandemi Covid-19: Studi pada Balita di Indonesia (Rapid Review) - Dwipajati -; Nurfarida Yuliana Agustin; Harisa Dian Nurani; Rizki Fitriani Ayundari (Amerta Nutrition, 2022)
Background: The prevalence of stunting under five in Indonesia is still below the government's target for 2024, which is 14%. The problem of the availability of food ingredients to make nutritious food as a result of a decrease in family income during the Covid-19 pandemic became the main factor in providing toddler food. Improper feeding of toddlers can affect the growth and development of toddlers including stunting. The main components of toddler feeding according to WHO standards consist of time to introduce food, diversity of food ingredients, frequency of feeding, breastfeeding up to 2 years, and sanitation hygiene in preparing toddler food. However, the components of toddler feeding are still very diverse. Objective: To examine the components of toddler feeding that can be used in efforts to prevent stunting in toddlers in Indonesia Discussion: Through the PubMed database, Science Direct, and Google Scholar with the keywords complementary feeding during covid, 11 observational studies were found with cross-sectional, case-control and case study designs Components in toddler feeding related to stunting during the Covid-19 pandemic are the introduction of food, minimum food diversity (MDD), minimum meal frequency (MFF), portion standards, and appetite. While the level of knowledge, family income, caregivers, history of breastfeeding, conducive eating situations, and the use of instant porridge are other components that have the potential to cause stunting in toddlers. Conclusion: The introduction of food, a certain amount of variety in the diet, and a minimum number of meals per day are the general elements of toddler feeding that must be taken into account in order to prevent stunting during a pandemic.